Ekonomi Kreatif dan Pembangunan Ekonomi : Sebuah Tinjauan Literatur tentang Peran dan Kontribusi - Rindyi Putri Lestari; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The creative economy has been a much-discussed topic in terms of economic development over the past few years. The concept refers to economic activities that involve creativity, knowledge, and skills to generate added value. This study aims to analyze the role and contribution of the creative economy to economic development in a country. A literature review was conducted to understand the concepts of creative economy, economic development, and the relationship between the two variables. Data were collected from various sources, such as books, scientific papers, and journals relevant to the research topic. The results of the literature review analysis show that the creative economy has a significant role and contribution to economic development, where it has great potential in economic growth, job creation, and improving people's welfare.